Applying of intergral parameters of multidimensional objects to solve the medical and biological problems. - Dyagovets, K. I.; Marchenko, D. G.; Morozova, S. B.; Petruk, N. S.; Romanenko, L. A.; Stanishevska, N. V.; Sultanova, N. M.; Filimonova, L. A.; Khrіpkov, I. S.; Shamelashvili, K. L.; Shevchenko, K. M.; Tverdokhlib, I. V. (Морфологія / Morphologia / Morfologìâ, 2016)
The article points out at certain mistakes and limitations of extensive approach towards the choice of mathematical instrument for biometrics processing of medical and biologic research results. Out of the necessity to operate generalizing properties of processes and events, it is suggested to use polythetic cluster analysis for determining integral parameters of the objects considering all properties of interest as well as mathematical determination of the degree of significance of each of them. Two types of tasks are marked out that could be easily solved by means of the suggested procedure: polythetic classification and object integral parameters comparison.